The use of learning management systems in ESP to explore postgraduate students' content knowledge about epidemiology and COVID-19: a mixed-methods study - Mohammed El Messaoudi (ÜNİVERSİTEPARK Limited, 2021)
Background/purpose - This sequential explanatory mixed-methods study inspected the impact of an online ESP course on postgraduate students' content knowledge development about epidemiology in general and COVID-19 in particular. The course was titled "English for Pandemics" and was administered via a Learning Management System (Edmodo). Materials/methods - Needs Analysis was (informally) deployed to trace participants' needs, preferences, and wants in order to shape the landscape of the treatment. The researcher employed a quasi-experimental design (a one-group, pretest-posttest design). Participants were pretested prior to the treatment. The treatment consisted of online exposure to eight units (English for Pandemics), capitalizing on Edmodo in content delivery, receipt, mastery, and assessment. Following the treatment, after 8 weeks, the participants were post-tested. Results - Quantitative results revealed a statistically significant difference in the participants' content knowledge regarding epidemiology and COVID-19. Qualitative findings divulged that participants highly appreciated Edmodo interactive features (simplicity, functionality, control, communal learning, and real-time feedback), and voiced their readiness to opt for Edmodo in future learning experiences. Conclusion - Based on empirical evidence, the current study argues that the Edmodo learning management system has the potential to push content delivery, receipt, mastery, and assessment in ESP courses to the next level.